A neural perspective on the treatment of hypertension: the neurological network excitation and inhibition (E/I) imbalance in hypertension - Xia, Min; Wang, Tianyu; Wang, Yizhu; Hu, Tingting; Chen, Defang; Wang, Bin (Frontiers in Cardiovascular Medicine, 2024)
Despite the increasing number of anti-hypertensive drugs have been developed and used in the clinical setting, persistent deficiencies persist, including issues such as lifelong dosage, combination therapy. Notwithstanding receiving the treatment under enduring these deficiencies, approximately 4 in 5 patients still fail to achieve reliable blood pressure (BP) control. The application of neuromodulation in the context of hypertension presents a pioneering strategy for addressing this condition, con-currently implying a potential central nervous mechanism underlying hypertension onset. We hypothesize that neurological networks, an essential component of maintaining appropriate neurological function, are involved in hypertension. Drawing on both peer-reviewed research and our laboratory investigations, we endeavor to investigate the underlying neural mechanisms involved in hypertension by identifying a close relationship between its onset of hypertension and an excitation and inhibition (E/I) imbalance. In addition to the involvement of excitatory glutamatergic and GABAergic inhibitory system, the pathogenesis of hypertension is also associated with Voltage-gated sodium channels (VGSCs, Nav)-mediated E/I balance. The overloading of glutamate or enhancement of glutamate receptors may be attributed to the E/I imbalance, ultimately triggering hypertension. GABA loss and GABA receptor dysfunction have also proven to be involved. Furthermore, we have identified that abnormalities in sodium channel expression and function alter neural excitability, thereby disturbing E/I balance and potentially serving as a mechanism underlying hypertension. These insights are expected to furnish potential strategies for the advancement of innovative anti-hypertensive therapies and a meaningful reference for the exploration of central nervous system (CNS) targets of anti-hypertensives.